2019
DOI: 10.1177/0261927x19883899
|View full text |Cite
|
Sign up to set email alerts
|

Italian With an Accent: The Case of “Chinese Italian” in Tuscan High Schools

Abstract: Two experiments test the existence of prejudicial attitudes toward nonnative Italian speech (specifically Chinese-accented Italian) within Tuscany’s high schools, among teachers and student samples. The research explores and integrates different methodologies: explicit inquiry (overt questionnaires) as well as implicit tests (Implicit Association Test protocol). The results outlined the existence of significant implicit negative attitudes toward Chinese-accented Italian and established the discrepancy between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Currently, students with Chinese migration background in Italian schools are more likely to have lower levels of academic performance and language acquisition (ISTAT, 2020). This is a particularly acute issue, especially when teachers in Italian public schools generally lack an awareness of multilingual promotion and didactic skills/resources to address challenges faced by non‐native students (Calamai & Ardolino, 2020). The services of Italian grammar classes offered by the educational organisations analysed in this study provide a partial solution to help young generations better integrate in local Italian school life and eventually equipping them with the necessary skills to participate in Italian public debates and social events.…”
Section: Policy Implications Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, students with Chinese migration background in Italian schools are more likely to have lower levels of academic performance and language acquisition (ISTAT, 2020). This is a particularly acute issue, especially when teachers in Italian public schools generally lack an awareness of multilingual promotion and didactic skills/resources to address challenges faced by non‐native students (Calamai & Ardolino, 2020). The services of Italian grammar classes offered by the educational organisations analysed in this study provide a partial solution to help young generations better integrate in local Italian school life and eventually equipping them with the necessary skills to participate in Italian public debates and social events.…”
Section: Policy Implications Of Findingsmentioning
confidence: 99%
“…Their study uncovered the difficult and conflicted process of identity-building, as often constrained by the hostile narrative and attitude of the host society. For instance, Calamai and Ardolino (2020) found how high school teachers in Prato not only are unprepared to address multilingual opportunities and challenges in education, but also express implicit preferences for "unaccented" Italian speakers over Chinese-accented speakers. Marsden's (2011) investigation showed the offspring of Chinese migrants as being stigmatised, forcing them to take over the role of mediators between the Chinese and Italian societies.…”
Section: Chine S E Communitie S In Italymentioning
confidence: 99%
“…The sensitivity toward nonstandard speech is evident in early childhood, for instance, with nonnative accented speakers being less trusted and less often offered friendship (e.g., Kinzler, Dupoux, & Spelke, 2007, see also Calamai & Ardolino, 2020 for negative consequences in the educational setting). Having a foreign or nonstandard accent has also proven negative in professional settings (e.g., Huang, Frideger, & Pearce, 2013), with accented speakers being less eagerly hired and/or assigned lower salaries (Gluszek & Dovidio, 2010), and less likely recommended for promotion (Hosoda & Stone-Romero, 2010).…”
Section: Negative Consequences Of Nonstandard Speechmentioning
confidence: 99%
“…This ability to distinguish us from them based on subtle vocal cues is present even among infants, with newborns as young as 4 days discriminating utterances in their native language from those in a foreign language (Mehler et al, 1988). Belonging to the accented them usually triggers a negative evaluation from listeners belonging to the linguistically normative group (Calamai & Ardolino, 2020). Since the initial evidence advanced by Lambert, Hodgson, Gardner, and Fillenbaum (1960), a consistent line of research involving several languages has confirmed that accented speakers are rated less favorably than standard speakers (Lindemann, 2005; for a comprehensive review, see Giles & Watson, 2013, or Gluszek & Dovidio, 2010).…”
Section: Introduction To the Special Issuementioning
confidence: 99%
“…This ability to distinguish us from them based on subtle vocal cues is present even among infants, with newborns as young as 4 days discriminating utterances in their native language from those in a foreign language (Mehler et al, 1988). Belonging to the accented them usually triggers a negative evaluation from listeners belonging to the linguistically normative group (Calamai & Ardolino, 2020). Since the initial evidence advanced by Lambert, Hodgson, Gardner, and Fillenbaum (1960), a consistent line of research involving several languages has confirmed that accented speakers are rated less favorably than standard speakers (Lindemann, 2005; for a comprehensive review, see Giles & Watson, 2013, or Gluszek & Dovidio, 2010.…”
Section: Introduction To the Special Issuementioning
confidence: 99%